Integration of organic dye technology in the development of solar devices - Khan, Nabeela Sarwar (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.